HUBUNGAN REAKSI, KOORDINASI, DAN KONSENTRASI TERHADAP KETEPATAN PUKULAN DRIVE DALAM PERMAINAN SQUASH PADA ATLET PUTRA SQUASH RIAU - Arief, Muhammad; Sulastio, Agus; S, Wedi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aims to determine the relationship between reaction,coordination, and concentration on the accuracy of the drive punch in the game ofsquash in Riau male squash athletes. Squash is a sport that requires high technicalskills and adequate physical support. This study uses a descriptive method with acorrelational approach to measure and analyze relationships between variables. Thepopulation in this study was Riau male squash athletes totaling 20 people, with aresearch sample of 7 athletes selected by purposive sampling based on certain criteria. Research instruments include reaction tests using the Whole Body Reaction Test, eye-hand coordination tests with Catch Ball Throws, and concentration tests using the Grid Concentration Test. In addition, the accuracy of the drive stroke is measured through a validated squash playing skill test. The data were analyzed using the Pearson correlation with a significance level of 0.05.The results showed a significant relationship between reaction, coordination, and concentration on the accuracy of the hit drive in a squash game. Quick reactions, good eye-hand coordination, and high concentration contribute positively to the athlete's ability to execute precise drive strokes. This research is expected to contribute to the field of squash coaching, especially in improving the skills and achievements of athletes through more focused training program.Key Words: Reaction, Coordination, Concentration, Precision Punch Drive, Squash